Antibodies Against Glycolipids Enhance Antifungal Activity of Macrophages and Reduce Fungal Burden After Infection with Paracoccidioides brasiliensis - Bueno, Renata A.; Thomaz, Luciana; Muñoz, Julian E.; da Silva, Cássia J.; Nosanchuk, Joshua D.; Pinto, Márcia R.; Travassos, Luiz R.; Taborda, Carlos P. (Frontiers in Microbiology, 2016)
Paracoccidioidomycosis is a fungal disease endemic in Latin America. Polyclonal antibodies to acidic glycosphingolipids (GSLs) from Paracoccidioides brasiliensis opsonized yeast forms in vitro increasing phagocytosis and reduced the fungal burden of infected animals. Antibodies to GSL were active in both prophylactic and therapeutic protocols using a murine intratracheal infection model. Pathological examination of the lungs of animals treated with antibodies to GSL showed well-organized granulomas and minimally damaged parenchyma compared to the untreated control. Murine peritoneal macrophages activated by IFN-γ and incubated with antibodies against acidic GSLs more effectively phagocytosed and killed P. brasiliensis yeast cells as well as produced more nitric oxide compared to controls. The present work discloses a novel target of protective antibodies against P. brasiliensis adding to other well-studied mediators of the immune response to this fungus.